Emde, Coolen, dan Istrinya: Analisis Gender dan Relasi Kuasa dalam Pekabaran Injil di Jawa Timur (1812-1848) - Maria Theofani Widayat (KENOSIS: Jurnal Kajian Teologi, 2021)
This article aims to build awareness of the gender equality issues in the history of Christianity through historical research. The subject of the research is the history of missions in East Java, especially in 1812-1848. Therefore, this study employs an analysis of gender and power relations both through feminist theory initiated by Kwok Pui Lan and also orientalism theory brought by Edward Said in examining the history of mission in East Java on that period. The characters appointed as the research subjects are Johannes Emde and Coenrad Laurens Coolen, along with their wives and children. They are the pioneers in introducing the gospel to the Javanese in East Java, thus become the foundations of the Christian community in East Java. In particular, the life of Emde and Coolen are so intertwined with the history of the East Java Christian Church (GKJW). However, there is a gender gap found in the mission by Emde and Coolen. In response, this research is conducted to keep building the awareness of gender justice as the history of Christianity carry on.AbstrakTulisan ini adalah bentuk upaya membangun kesadaran terhadap keadilan gender atas sejarah Kekristenan melalui penelitian pada sejarah pekabaran Injil di Jawa Timur khususnya pada tahun 1812-1848. Untuk itu penelitian ini menggunakan analisis gender dan relasi kuasa melalui teori feminis yang digagas oleh Kwok Pui Lan dan teori orientalisme yang dibawa oleh Edward Said dalam menelaah sejarah pekabaran Injil di Jawa Timur pada periode tersebut. Tokoh-tokoh yang diangkat adalah Johannes Emde dan Coenrad Laurens Coolen, beserta istri dan anaknya. Mereka memiliki andil besar dalam mengenalkan Injil dan menjadi pondasi komunitas Kristen di Jawa Timur. Utamanya tokoh Emde dan Coolen yang begitu melekat pada sejarah Greja Kristen Jawi Wetan (GKJW). Namun dalam proses pekabaran Injil yang dilakukan oleh Emde dan Coolen lekat dengan ketimpangan gender. Oleh karena itu, penelitian ini dilakukan supaya terus terbangun kesadaran pada keadilan gender dalam membaca dan melanjutkan sejarah Kekristenan di mana saja.